The disease burden of viral encephalitis in China between 1990 and 2019 - Shan-Shan HUANG; Wu-Ming ZHOU; Min-Jie WANG; Yu-Qian CHU; Meng-Ke JIANG; Min YANG (Yixue xinzhi zazhi)
Objective To explore changes in disease burden of viral encephalitis (VE) in China between 1990 and 2019 and compare this with the global situation over the same period, so as to provide direc-tion for effective prevention and control strategies.Method Based on the data from the Global Burden of Diseases 2019 survey (GBD 2019), the incidence, prevalence, mortality, years lived with disability (YLD) rate, years of life lost (YLL) rate and their standardized rates were analyzed and compared with global changes.Result In 2019, the incidence, prevalence, mortality, YLD and YLL rate of VE in China were 15.27/100,000, 74.34/100,000, 0.24/100,000, 7.29/100,000 and 13.40/100,000, which de-creased by 27.18%, 33.42%, 70.00%, 40.29% and 78.56% respectively, which compared with that of 1990. In 2019, the remaining standardized indicators in China exceeded the global level except the standardized mortality and YLL rate. In 2019, the standardized incidence, prevalence, mortality, YLD and YLL rate of males in China were 22.81/100,000, 73.74/100,000, 0.34/100,000, 7.46/100,000 and 22.26/100,000 respectively, which were higher than those of females in the same period. Similar to 1990, the incidence and mortality rate among Chinese between 0~4 years old were higher compared with those in other age groups. The incidence and mortality rate among people over 50 years old were gradually increasing.Conclusion As of 2019, the overall disease burden of VE in China was high. While actively reducing the risk of infection, attention should also be paid to laboratory examination at the early stage of the disease, timely detection, early diagnosis and treatment, and active control of the dis-ease development. Children and elderly men should be the focus of attention.